2013
DOI: 10.1136/bmj.f5446
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and cardiovascular disease mortality in east Asians and south Asians: pooled analysis of prospective data from the Asia Cohort Consortium

Abstract: Objective To evaluate the association between body mass index and mortality from overall cardiovascular disease and specific subtypes of cardiovascular disease in east and south Asians.Design Pooled analyses of 20 prospective cohorts in Asia, including data from 835 082 east Asians and 289 815 south Asians. Cohorts were identified through a systematic search of the literature in early 2008, followed by a survey that was sent to each cohort to assess data availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
186
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(202 citation statements)
references
References 87 publications
13
186
0
3
Order By: Relevance
“…Our study coincides with the results of P. Jeemon and K. S. Reddy. 17 Almost 12% (24) subjects under study were found to had a positive family history of cardiovascular diseases and the remaining 72% (36) subjects had no family history of CVD. Our study demonstrated the same results as by Arvind K et al 18 suggested that family history may have a "dose-dependent" effect, where individuals with more robust family histories of CHD are at greater risk of developing CVDs.…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…Our study coincides with the results of P. Jeemon and K. S. Reddy. 17 Almost 12% (24) subjects under study were found to had a positive family history of cardiovascular diseases and the remaining 72% (36) subjects had no family history of CVD. Our study demonstrated the same results as by Arvind K et al 18 suggested that family history may have a "dose-dependent" effect, where individuals with more robust family histories of CHD are at greater risk of developing CVDs.…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…The inconsistent association of BMI and CVD has been previously reported. High BMI was found to be weak risk factor for mortality from cardiovascular disease in south Asians [17] . Fluctuating body weight rather than obesity has been associated with risk of stroke and increased mortality [18] .…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies conducted in other parts of the world also show similar evidences. [6][7][8][9] Commonest complication of CAG in our study group is haematoma. 15% patients had haematoma out of 100 patients.…”
Section: Discussionmentioning
confidence: 99%